Hubungan Dukungan Keluarga dengan Perawatan Diri pada Lansia Diabetes Melitus Tipe 2 di Puskesmas Kedungmundu - Nabilatun Khasanah; Moch. Aspihan; Iskim Luthfa (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Self-care is an individual's effort to manage their health condition, especially for people with diabetes mellitus, to keep blood sugar levels under control. One element that influences the effectiveness of self-care is family support. This support can take various forms, such as emotional support, practical assistance, information, and evaluative feedback. This study aims to explore the relationship between family support and self-care practices in elderly people with type 2 diabetes mellitus at the Kedungmundu Health Center. This study design is correlational with a cross-sectional approach. The sample taken consisted of 68 elderly people with type 2 DM who visited the Kedungmundu Health Center. The sample selection used a purposive sampling technique. The inclusion criteria involved outpatients who lived with their families. The instruments used in this study were a questionnaire about family support and SDSCA (Summary of Diabetes Self-Care Activities). To analyze the data, the chi-square test was used in bivariate analysis. The results showed that 60.3% of respondents received positive family support, while 48.5% of respondents showed good self-care practices. Further analysis showed a significant relationship between family support and self-care practices with a p value of 0.000 (p <0.05). Conclusion: Based on the results found, it can be concluded that family support plays an important role in improving the quality of self-care in elderly people with type 2 diabetes mellitus.